Role of oral and gut microbiomes in enterosalivary nitrate metabolism and their effects on systemic disease - Yang, Zi; Du, Conglin; Chang, Zhichao; Yang, Yang; Hu, Liang (Frontiers in Cellular and Infection Microbiology, 2025)
Nitrate, which maintains hemostasis in systemic circulation, is obtained from nitrate-rich vegetables, concentrated, reabsorbed by the salivary glands, and reduced to nitrite and nitric oxide (NO•). The bioavailability of nitrate and nitrite depends on unique nitrate reductases present in specific bacterial communities in the mouth and gut of mammals. The dominant bacteria in the oral cavity, stomach, and gut differ among internal environments. Nitrate can modulate microbiota metabolism and has important pathophysiological functions in diseases such as cardiovascular diseases, gastrointestinal diseases, diabetes, metabolic diseases, and brain diseases via nitrate-reducing bacteria. Thus, in this review, we summarized the beneficial role of enterosalivary nitrate metabolism, focusing on the role of oral and gut bacterial communities in the enzymatic reduction of nitrate to nitrite. We have also discussed different nitrate-reduction pathways; influencing factors of nitrate-reducing bacteria; and the relationship among systemic health, nitrate intake, and bacteria. This review of enterosalivary nitrate and related microbiomes could provide a new perspective for the application of nitrate.